Autonomic and Redox Imbalance Correlates With T-Lymphocyte Inflammation in a Model of Chronic Social Defeat Stress - Moshfegh, Cassandra M.; Elkhatib, Safwan K.; Collins, Christopher W.; Kohl, Allison J.; Case, Adam J. (Frontiers in Behavioral Neuroscience, 2019)
Patients diagnosed with post-traumatic stress disorder (PTSD) are at a significantly elevated risk of developing comorbid inflammatory conditions, but the mechanisms underlying this predilection remain unclear. Our previous work has shown that T-lymphocytes exposed to elevated levels of norepinephrine (NE) displayed a pro-inflammatory signature reminiscent of an autoreactive phenotype. With this, we hypothesized that the increased sympathetic tone observed during psychological trauma may be promoting pro-inflammatory T-lymphocytes, which causes a predisposition to comorbid inflammatory conditions. Here, we examined the consequences of psychological trauma on splenic T-lymphocytes using a mouse model of repeated social defeat stress. Social defeat led to anxiety-like and depression-like behavior as has been previously described. The spleens of socially-defeated mice showed significant elevations of NE, tyrosine hydroxylase, and acetylcholinesterase levels, which appeared to be due in part to increased expression within T-lymphocytes. Additionally, T-lymphocytes from stressed animals showed higher levels of pro-inflammatory cytokines and mitochondrial superoxide. Interestingly, in this model system, close associations exist within splenic T-lymphocytes amid the autonomic, inflammatory, and redox environments, but these only weakly correlate with individual behavioral differences among animals suggesting the psychological and physiological manifestations of trauma may not be tightly coupled. Last, we describe, for the first time, elevations in calprotectin levels within T-lymphocytes and in circulation of psychologically stressed animals. Calprotectin correlated with both behavioral and physiological changes after social defeat, suggesting the potential for a new biological marker and therapeutic target for PTSD and its inflammatory comorbidities.